The influence of constant temperature on population growth rates of the cassava mealybug, Phenacoccus manihoti - Lema, K.M.; Herren, H.R. (1985)
Life table studies were conducted to assess the effect of constant temperature on the rate of population growth of the cassava mealybug, Phenacoccus manihoti Matile‐Ferrero. Four temperatures, between 20 and 30.5 °C, were tested. An inverse relationship was observed between temperature and most demographic parameters.